Strength training practices in amateur and professional boxing - Beattie, K.; Ruddock, A. D. (The Journal of Strength and Conditioning Research, 2025)
Previous research has highlighted that force development are key contributors to punch impact force in boxing; however, the strength training practices within the sport remain unclear. Identifying such practices is an important first step in the development of accessible educational resources and recommendations to develop strength at all standards in boxing. The aim of this study was to investigate strength training practices in amateur and professional boxing. Seventy-two trainers or support staff working in amateur or professional boxing completed an online survey comprising of 7 sections: Study Information and Informed Consent, Subject Information, Perceptions of Strength Training, Strength Training Characteristics, Power Training Characteristics, and Strength and Power Assessment. Frequency analysis was used to report responses to fixed-response questions, and thematic analysis was applied to 1 open-ended question. The main findings of this study demonstrate that the majority of practitioners (a) implemented strength training to improve "punching power" and muscular endurance and reduce the likelihood of injury (72-88%); (b) used punch-specific and reactive-strength training the most in programming (93%); (c) acknowledged that maximal-strength training improves "punching power" (84%), yet programmed it the least in training; and (d) highlighted that there was a fear in boxing that maximum-strength training may lead to unwanted increases in muscle mass and cited a lack of resources as a reason for maximal-strength training not being used. As there is a large contingent of volunteer practitioners in boxing without professional S&C or sport science accreditations (78%), it is recommended that national governing bodies provide adequate training and education to practitioners.